Relative Performance of Seasonal Intercrops Grown in Association with Eucalyptus - Nadagouda, V. B.; Radder, G. D.; Desai, B. K.; Manjappa, K.; Patil, C. V. (Indian Forester, 1997)
A field experiment was conducted to study the effect of Eucalyptus on associated seasonal field crops under irrigation at Regional Research Station, Raichur, Karnataka, India. The saplings of Eucalyptus hybrid were planted by adopting 20 m Ã— 1 m spacing in north-south direction during 1983. Saplings were allowed to grow for five years. At the end of fifth year five seasonal crops viz., pearl millet, maize, groundnut, pigeonpea and cotton were raised in between Eucalyptus tree lines during Kharif 1988-89. The extent of adverse effect of Eucalyptus was maximum on maize and minimum on cotton. The yields were significantly higher on western side than on eastern side. The yield increase with every unit increase in distance for tree line was also found significant. The interaction effect of direction and distance from tree line on yield of various test crops was not significant.